Enhanced parallel thread scheduling for Java based applications on multi-core architecture - Kam-Mun, Chong; Hai-Shuan, Lam; Chikkannan, Eswaran (2008)
With the ability to execute more than one thread parallelly, the multi-core processor is claimed to deliver greater performance for multithreaded applications. The performance of thread scheduler in Java Virtual Machine has a profound impact on the performance of multithreaded Java applications. However, the lack of efficient thread scheduler in Java Virtual Machine creates burden in scheduling threads into parallel processors. Various enhancements on thread scheduler in JVM are proposed to boost up the performance of Java applications on dual-core processor. Affinity scheduling mechanism yields a 4% of throughput improvement. Priority scheduling mechanism helps in reducing the overhead incurred by 23.1%. These results shown the mechanisms suggested are efficient in delivering better performance on dual-core processor.